Criminal prosecution and punishment of migrants in Spain: A border criminology perspective. - García-España, Elisa (Sciendo, 2023)
The exceptional use of criminal law to achieve migration policy objectives has been a reality in Spain since the first Aliens Law was passed in 1985. Since then, academia has warned about the discriminatory and exclusionary effects of this confluence. This paper critically analyses a series of exceptional Spanish criminal and migration policy measures aimed at criminalising certain population movements. The aim is to show the mechanisms used by criminal justice in Spain to manage human mobility from the perspective of border criminology. Among other things, I will analyse (1) ‘hot returns’ and (2) racial profiling in police stops, both as police reactions. I will also study (3) the expulsion of convicted foreigners and (4) criminal records as a migration control strategy and, finally, the deprivation of liberty for migration control purposes, such as (5) detention centres for migrants and (6) prison release strategies. The aim is to show that Spanish penal policy, taken in a broad sense as all eminently criminal measures and those where criminal law and immigration law converge, has as its main objective to socially render harmless (innocuousation) foreign suspects, convicts and ex-convicts in Spain with different and exceptional measures that push them to the margins of society.
Fruto del Proyecto I+D sobre Jóvenes extranjeros extutelados en prisiones de Andalucía (P20-00381-R). Financiado con fondos de la Junta de Andalucía en la convocatoria competitiva Retos 2021-2023. IP. Elisa Garcia España
Keywords: Emigración e inmigración - Derecho y legislación - España; Expulsión de extranjeros; Emigración e inmigración - Política gubernamental - España; Critical criminology; Migration policy; Hot returns; Racial profiling; Border criminology; Social exclusion; Prison